Unroofing Curettage Versus Modified Limberg Flap in Pilonidal Disease: A Retrospective Cohort Study. Issue 10 (24th May 2022) - Sahin, Alpaslan; Simsek, Gurcan; Arslan, Kemal
Abstract : BACKGROUND: Sacrococcygeal pilonidal disease (estimated incidence, 25/100, 000) is a chronic inflammatory condition that commonly affects young adults. However, the ideal surgical treatment for this disease remains undetermined. OBJECTIVE: This study aimed to compare the results of the unroofing curettage and those of the modified Limberg flap surgical technique. DESIGN: This is a retrospective cohort study. SETTINGS: Procedures were performed by 2 surgeons between January 2013 and January 2017. PATIENTS: The data of 278 patients who underwent surgery for the treatment of pilonidal disease were analyzed. INTERVENTIONS: Unroofing curettage was performed under local or spinal anesthesia, whereas spinal anesthesia was used for the modified Limberg flap procedure. MAIN OUTCOME MEASURES: The primary outcome was recurrence rate. Secondary outcomes included adverse events, limitation of daily activities, and healing time. RESULTS: Between the 2 groups (unroofing curettage, n = 135; modified Limberg flap, n = 143), recurrence was lower in the unroofing curettage group after a 60-month median follow-up period, but the difference was not statistically significant (1.5% vs 4.2%, p = 0.45). The duration of surgery and length of hospital stay were shorter in the unroofing curettage group (11.44 ± 3.56 minutes vs 52.47 ± 7.92 minutes and 0.27 ± 0.45 days vs 1.07 ± 0.26 days, p < 0.001). Postoperative complications were significantly higher in the modified Limberg flap group (9.8% vs 2.2%, p = 0.009). The time required to return to work or school was shorter in the unroofing curettage group (8.6 ± 7.8 days vs 25.01 ± 6.3 days, p < 0.001). The complete healing time was longer in the unroofing curettage group (35.3 ± 9.2 days vs 23.2 ± 5.4 days, p < 0.001). LIMITATIONS: The retrospective study design was a limitation of this study. CONCLUSIONs: Unroofing curettage provided more clinical benefits than the modified Limberg flap approach. Unroofing curettage should be considered as the first choice of surgical treatment for pilonidal disease. See Video Abstract at http://links.lww.com/DCR/B824 . DESTECHAMIENTO Y CURETAJE VERSUS COLGAJO DE LIMBERG MODIFICADO EN LA ENFERMEDAD PILONIDAL: UN ESTUDIO DE COHORTE RETROSPECTIVE: ANTECEDENTES: La enfermedad pilonidal sacrococcígea (incidencia estimada, 25 / 100.000) es una enfermedad inflamatoria crónica que comúnmente afecta a adultos jóvenes. Sin embargo, el tratamiento quirúrgico ideal para esta enfermedad permanece indeterminado. OBJETIVO: Comparar los resultados del destechamiento y curetaje y los de la técnica quirúrgica con colgajo de Limberg modificado. DISEÑO: Estudio de cohorte retrospectivo. ENTORNO CLINICO: Los procedimientos fueron realizados por dos cirujanos, entre enero del 2013 y enero del 2017. PACIENTES: Se analizaron datos de 278 pacientes intervenidos quirúrgicamente para el tratamiento de la enfermedad pilonidal. INTERVENCIONES: Se realizó destechamiento y curetaje con anestesia local o raquídea, mientras que para el procedimiento de colgajo de Limberg modificado se utilizó anestesia raquídea. PRINCIPALES MEDIDAS DE RESULTADO: El resultado principal fue la tasa de recurrencia. Los resultados secundarios incluyeron eventos adversos, limitación de las actividades diarias y tiempo de curación. RESULTADOS: Entre los dos grupos (destechamiento y curetaje, n = 135; colgajo de Limberg modificado, n = 143), la recurrencia fue menor en el grupo con destechamiento y curetaje después de un período de seguimiento medio de 60 meses, pero la diferencia no fue estadísticamente significativa (1, 5% vs 4, 2%, p = 0, 45). La duración de la cirugía y la estancia hospitalaria fueron más cortas en el grupo de destechamiento y curetaje (11, 44 ± 3, 56 min vs a 52, 47 ± 7, 92 min y 0, 27 ± 0, 45 días vs 1, 07 ± 0, 26 días, p < 0, 001). Las complicaciones posoperatorias fueron significativamente mayores en el grupo de colgajo de Limberg modificado (9, 8% vs 2, 2%, p = 0, 009). El tiempo necesario para regresar al trabajo o la escuela fue menor en el grupo de destechamiento y curetaje (8, 6 ± 7, 8 días vs 25, 01 ± 6, 3 días, p < 0, 001). El tiempo de cicatrización completo fue mayor en el grupo de destechamiento y curetaje (35, 3 ± 9, 2 días vs 23, 2 ± 5, 4 días, p < 0, 001). LIMITACIONES: El diseño del estudio retrospectivo. CONCLUSIONES: El destechamiento y curetaje proporcionó más beneficios clínicos que el abordaje con colgajo de Limberg modificado. El destechamiento y curetaje debe considerarse como la primera opción de tratamiento quirúrgico para la enfermedad pilonidal. Consulte Video Resumen en http://links.lww.com/DCR/B824 . (Traducción— Dr. Francisco M. Abarca-Rendon )